Pengaruh Pemahaman Muamalah dan Sikap Heuristik Terhadap Pengambilan Keputusan Investasi Syariah pada Mahasiswa Universitas Islam Negeri Sumatera Utara (UINSU) - Fudla Azzuhra Rahmawan; Nur Ahmadi Bi Rahmani; Purnama Ramadani Silalahi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to examine the effect of muamalah understanding and heuristic attitude on sharia investment decision making among students of the Faculty of Economics and Islamic Business at the State Islamic University of North Sumatra (UINSU). Muamalah understanding refers to the knowledge of Islamic rules governing economic transactions, including the prohibition of riba, gharar, and maisir. Meanwhile, heuristic attitude involves the use of rules of thumb that help simplify the decision-making process, especially in complex and uncertain situations. This study was conducted using a quantitative approach through a survey of 271 students selected using purposive sampling technique. Data was collected through a Google Form-based questionnaire and analysed using multiple linear regression. The results showed that both muamalah understanding and heuristic attitude have a significant positive influence on Islamic investment decision making. Simultaneously, these two variables explain about 67,0% of the variation in Islamic investment decision-making. A deep understanding of muamalah helps students in choosing investments that are in accordance with sharia principles, while heuristic attitude allows them to make decisions more quickly and efficiently even in conditions of limited information.